Converts in the Dead Sea Scrolls: the Ger in the Dead Sea scrolls (Studies on the texts of the desert of Judah, Volume 126, 2018)
Description Not Provided

Christian origins and the establishment of the early Jesus movement (Texts and editions for New Testament study. Early Christianity in its hellenistic context, Volume 4,, 2018)
Description Not Provided

Calculus for cranks (Yale University Press, 2021)
Description Not Provided

Metal-catalyzed nh and oh insertion from -diazocarbonyl compounds (Logos Verlag Berlin, 2019)
Description Not Provided

Autonomie, Bildung und Okonomie: Theorie und Praxis im Fremdsprachenunterricht (Romanische Sprachen und ihre Didaktik, Volume 69,, 2019)
Description Not Provided

El crimen de la guerra (Linkgua Pensamiento, ,, 2016)
Description Not Provided

Untersuchung thermoakustischer Instabilitaten von Sprayflammen (Forschungsberichte aus dem Institut fur Thermische Stromungsmaschinen, Band 72,, 2018)
Description Not Provided

CO2-Abtrennung in Kraftwerks-und Industrieanlagen und Transport des CO2 in einem gemeinsamen Pipelinesystem (Cuvillier Verlag, 2019)
Description Not Provided

Im Namen des Pazifismus: Wassili W. Wereschtschagin und Bertha von Suttner (Ost-West-Express. Kultur und Ubersetzung, Band 38,, 2020)
Description Not Provided

Traumatisierung durch Krieg, Flucht und Migration: Der Stellenwert der Psychologie im Umgang mit Betroffenen (Ibidem Verlag, 2012)
Description Not Provided

The stokes and navier-stokes equations in exterior domains: moving domains and decay properties (Logos Verlag Berlin, 2019)
Description Not Provided

Oneness pentecostalism: race, gender, and culture (The Pennsylvania State University Press, 2023)
Description Not Provided

Hugo grotius, annals of the war in the low countries (Leuven University Press, 2023)
Description Not Provided

Aufgabensammlung zur Statistik (NWB Studium Betriebswirtschaft, ,, 2013)
Description Not Provided

Emma goldman, mother earth, and the anarchist awakening (University of Notre Dame Press, 2021)
Description Not Provided

Verwendung mizellarer Systeme zur Synthese von Metallphosphat-Nanocontainern und nanoporosen Metallnitriden (Cuvillier Verlag, 2019)
Description Not Provided

A constellation of authority: Castilian Bishops and the Secular Church during the reign of Alfonso VIII (The Pennsylvania State University Press, 2023)
Description Not Provided

Neue Katalysatoren fur die Hydroaminierung von Alkenen und Alkinen (Cuvillier Verlag, 2015)
Description Not Provided

Die rechtliche Verbindlichkeit von Standardisierungsnormen am Beispiel von EN 13850 (Cuvillier Verlag, 2015)
Description Not Provided

Strukturelle Untersuchungen an Lignin-basierten Carbonfasern (Cuvillier Verlag, 2019)
Description Not Provided